(untitled) (Periphērica, 2024)
“El relato indefendible” was originally published in 1973 and included in Museo del chisme (2005) and Nuevo museo del chisme (2013). Edgardo Cozarinsky, Argentine writer, critic, and filmmaker, was born in 1939 into a Jewish Ukrainian immigrant family. His career was marked by wide-ranging and impactful contributions to several fields. He studied literature at the University of Buenos Aires and later collaborated with Silvina Ocampo, Adolfo Bioy Casares, and Jorge Luis Borges. He founded a film criticism review, Flashback, and proceeded to direct a series of critically acclaimed feature films from Les Apprentis Sorciers (1977) to Ronda nocturna (2005), including … (1971) also known as Puntos suspensivos, his “most notorious work,” which premiered at the Cannes Film Festival. During his time living in Paris and Buenos Aires, he wrote extensive collections of film criticism, short fiction, creative non-fiction, literary criticism, and novels. His Vudú urbano (1985), a hybrid literary-essayistic work, was prologued by Guillermo Cabrera Infante and Susan Sontag. In the 1970s, Cozarinsky received the best essay prize from the newspaper La Nación for his erudite and sprightly poststructuralist essay “El relato indefendible,” translated here. This essay—later included in Cozarinsky’s gossip anthologies Museo del chisme (2005) and Nuevo museo del chisme (2013)— theorizes the cultural practice of gossip, previously considered reprehensible and vulgar, unfolding and appreciating its participation in all literary practice, especially in the works of Marcel Proust, Henry James, and Jorge Luis Borges. As Cozarinsky says, “In its circulation, in its modification, gossip reproduces the general movement of history and human knowledge, as well as the movement of that narrative practice that is a feature of that knowledge and a metaphor for that history.” Surviving a cancer diagnosis in the 1990s, Cozarinsky continued to write prolifically and to affectionately guide a generation of literary and cultural contributors until his death in June 2024.